Asia's new regionalism and global role agenda for the East Asia summit - Kumar, Nagesh; Kesavapany, K.; Chaocheng, Yao (Research and Information System for Developing Countries ; Distributed in India by Bookwell, 2008)
Contributed articles presented at a series of conferences held at various places between 2004-2005.